2010
DOI: 10.1111/j.1365-2109.2009.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary docosahexaenoic acid (22:6n-3) and arachidonic acid (20:4n-6) on the growth, survival, stress resistance and fatty acid composition in black sea bass Centropristis striata (Linnaeus 1758) larvae

Abstract: The objectives of this study were to determine the effects of the dietary docosahexaenoic acid (DHA) to arachidonic acid (ARA) ratio on the survival, growth, hypersaline stress resistance and tissue composition of black sea bass larvae raised from ¢rst feeding to metamorphic stages. Larvae were fed enriched rotifers Brachionus rotundiformis and Artemia nauplii containing two levels of DHA (0% and10% total fatty acids 5 TFA) in conjunction with three levels of ARA (0%, 3% and 6% TFA). On d24ph, larvae fed the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 48 publications
4
50
0
1
Order By: Relevance
“…Our result indicated that inclusion of soybean oil in feed does not compromise the species growth, suggesting the possible replacement of fish oil with soybean oil in diet formulation for darkbarbel catfish. The positive relationship between tissue fatty acid composition and dietary fatty acid contents has been well demonstrated in previous studies (Bransden et al, 2005;Zia-Ul-haq et al, 2007a, b, 2008, 2011aLuo et al, 2008;Rezek et al, 2010). In this study, the muscle fatty acid composition in fish generally reflected the lipid composition in diets similar to the report of Ng et al (2003) that the high fatty acids in feed can lead to high fatty acids in muscle.…”
Section: Discussionsupporting
confidence: 71%
“…Our result indicated that inclusion of soybean oil in feed does not compromise the species growth, suggesting the possible replacement of fish oil with soybean oil in diet formulation for darkbarbel catfish. The positive relationship between tissue fatty acid composition and dietary fatty acid contents has been well demonstrated in previous studies (Bransden et al, 2005;Zia-Ul-haq et al, 2007a, b, 2008, 2011aLuo et al, 2008;Rezek et al, 2010). In this study, the muscle fatty acid composition in fish generally reflected the lipid composition in diets similar to the report of Ng et al (2003) that the high fatty acids in feed can lead to high fatty acids in muscle.…”
Section: Discussionsupporting
confidence: 71%
“…However, low survival in the Algamac 3080 treatment may also contribute to the high SGR due to the death of small larvae in this treatment. Highly unsaturated fatty acids, especially EPA, DHA, and ARA, are essential to growth, development, and survival in marine fish (Sargent et al 1999b;Cahu et al 2003a;Rezek et al 2010). To develop lipidenriched food for fish larvae, the requirements of essential fatty acids in fish larvae have been extensively studied by using live prey enriched with different oils and micronutrients, aiming to increase the essential fatty acids content in live prey (Sargent et al 1997;Takeuchi 1997;Izquierdo et al 2000).…”
Section: Discussionmentioning
confidence: 97%
“…In marine fish larvae, both DHA and EPA in the diet are essential to fish growth (Rezek et al 2010). Improvement in fish growth with increasing levels of dietary DHA has been observed in species such as yellowtail Seiola quiqueradiata (Furuita et al 1996), striped jack Caranx vinctus , and Japanese flounder Paralichthys olivaceus (Izquierdo et al 1992).…”
Section: Discussionmentioning
confidence: 98%
“…In marine fish larvae both DHA and EPA in the diet are essential for fish growth (Rezek et al, 2010). Improved fish growth with increasing levels of dietary DHA has been observed in species such as yellowtail, Seiola quiqueradiata (Furuita et al, 1996), striped jack Caranx vinctus and Japanese flounder Paralichthys olivaceus (Izquierdo et al, 1992).…”
Section: P<005)mentioning
confidence: 99%
“…Highly unsaturated fatty acids, especially EPA, DHA and ARA are essential for growth, development and survival in marine fish (Sargent et al, 1999;Cahu et al, 2003;Rezek et al, 2010). To develop lipid enriched food for fish larvae, the requirements of essential fatty acids in fish larvae have been extensively studied using live prey enriched with different oils and micro-nutrients, aiming to increase the essential fatty acids content in live prey Takeuchi, 1997;Izquierdo et al, 2000).…”
Section: P<005)mentioning
confidence: 99%